Una contribución para el debate sobre los populismos latino-americanos: “Caesarism and Bonapartism in Gramsci” de Francesa Antonini - Gómez, Sebastián (International Gramsci Journal, 2023)
This is the Abstract of the Spanish-language review by Sebastián Gómez of the book by Francesca Antonini Caesarism and Bonapartism in Gramsci published by Brill, Leiden and Boston, 2022.